Performance Analysis of Mobility Pattern for Vehicular Ad-Hoc Network Using Various Routing Protocols - Mishra, Richa; Choudhari, Sachin (International Journal of Computer Sciences and Engineering, 2025)
The network technology which is used to form a communication network by the use of cars as mobile nodes is known as Vehicular Ad-hoc Network (VANET).In VANET, there is a very important and significant role of routing protocols. The protocol helps to find out the performance of all those packets which are received and send between the mobile nodes. In this paper, we consult the performance of routing protocols over Constant Bit Rate data type with the help of Destination-Sequenced Distance Vector routing protocol (DSDV). The main focus of this paper is to compare and examine the best routing protocol so as to secure the network in future. For validate result , DSDV performs with all other evaluated protocols.